Part 5c: Solvent chemistry: solubility of CO2 in reactive solvents for post-combustion CO2. Issue 5 (October 2012) - Rayer, Aravind V; Sumon, Kazi Z; Sema, Teerawat; Henni, Amr; Idem, Raphael O; Tontiwachwuthikul, Paitoon
Concerns about climate change have propelled research efforts to develop affordable and environmentally benign technologies to capture CO2 from large emission sources, which can subsequently be used either for enhanced oil recovery or stored in other geological storage sites. The study of the solubility of CO2 in solvents is therefore of great interest, both from the theoretical and practical points of view. To screen solvents or to design CO2 capture processes, knowledge of the equilibrium solubility of CO2 in the solvents is necessary. A large body of solubility data of CO2 in aqueous and non-aqueous solutions of prominent industrial amines are available in literature. We present such data along with a description of the experimental techniques and thermodynamic models used. Innovations made to obtain an optimum solubility of CO2 and to minimize the energy cost of a desired CO2 capture system by adopting different kinds of solvents are also reviewed.